Unveiling the hidden threat of microplastics to coral reefs in remote South Atlantic islands - Rani-Borges, Bárbara; Gomes, Erandy; Maricato, Guilherme; Lins, Luís Henrique França de Carvalho; Moraes, Beatriz Rocha de; Lima, Gislaine Vanessa; Côrtes, Luís Guilherme França; Tavares, Marcos; Pereira, Pedro Henrique Cipresso; Ando, Rômulo Augusto; Queiroz, Lucas Gonçalves (The Science of the total environment, 2023)
The widespread presence of marine microplastics (< 5 mm) is a significant concern, as it may harm marine biodiversity and ocean ecosystems. Corals' capacity to ingest microplastics has emerged as a significant threat to reef ecosystems, owing to the detrimental physiological and ecological effects it can trigger. The extent of the impact of microplastics on Brazilian corals remains unclear and this study aimed to investigate its distribution and characteristics in four coral species: Favia gravida, Mussismilia hispida, Montastrea cavernosa, and Siderastrea stellata, found in the Trindade and Martim Vaz Islands – the most isolated archipelago of Brazil, located about 1200 km (680 miles) east of the coast. This study aims to reveal the extent of microplastic distribution in the coral reef environment, assess the amount of microplastics in different coral species, and compare each species' capacity to adhere and accumulate microplastics. A high concentration of ingested and adhered microplastics was detected in all coral species evaluated in the present study. No significant differences were observed in the sampling points which indicates that although the sampling points are located at different distances from the coast, the microplastic pollution is equally distributed in the region. Polyethylene (PE), polyvinyl chloride (PVC), polypropylene (PP), poly(methyl methacrylate) (PMMA), Rayon, and Nylon particles were detected, with a predominance of PE (45.5 %). No significant differences in microplastic concentration were detected among the various species and locations studied. Our research presents findings that demonstrate the extensive occurrence of microplastic contamination in coral colonies located on remote islands. [Display omitted] •Microplastic abundance was studied in remote Atlantic Island corals.•Microplastic adhesion and intake were not species-specific or site-specific.•Microplastics ranging from 100 to 300 μm were the most abundant.•The most predominant type were PE microplastics and fiber shaped.•The species most prone to adherence was M. cavernosa to intake was M. hispida.